ERISTOLAR GENRE: A MATTER OF STUDYING DIPLOMATIC RELATIONS AND ENVIRONMENTAL ISSUES - D.Kh. Sangirova (Galaxy International Interdisciplinary Research Journal, 2021)
The article draws the history of a letter into the scope of research and focuses on its theoretical and practical study. The letter was written between the Bukhara Ashtarkhani and the Safavid rulers of Iran. King Abbas’s reply to Nadr Muhammad Khan’s letter testifies to the history of diplomatic relations between the two countries. The king wrote to the khan that the conditions associated with the cooling of the climate had caused him to be unable to deliver the “requested horses”. The persistence of the cold climate has been shown to be one of the factors contributing to the strained relations between states in the region.